Impact of Cyberbullying in a Compulsory Secondary Education School - González, Manuel Ceballos; Núñez, María Luisa Parody; Núñez, Manuel Parody (Psychology in the schools, 2025)
ABSTRACT In this paper, we focus on describing the concept of cyberbullying and identifying the kind and impact of cyber‐victimization in terms of the gender and school stage in a sample of 173 students of the first and second course of Compulsory Secondary Education (students between 12 and 16 years old) of Colegio Sagrado Corazon from Málaga. To do so, we have used a Cyberbullying form classifying the assaults in several types: verbal‐written, visual, identity fraud and exclusion. The results have shown higher levels of cyber‐victimization in the male gender and in the last school stages. The most common assaults are verbal‐written. Summary Schools should develop and enforce comprehensive anti‐cyberbullying policies that include clear definitions, preventative measures, and consequences. Regular training for staff and students on recognizing and addressing cyberbullying is essential to create a safe and supportive learning environment. Integrate digital literacy education into the curriculum to empower students with the knowledge and skills needed to navigate online interactions responsibly. Educating students on the ethical use of technology and the potential consequences of cyberbullying can reduce incidents. Establish accessible support systems for victims of cyberbullying, including counseling services, peer support groups, and anonymous reporting mechanisms. Ensuring that students feel supported and heard can mitigate the psychological impact of cyberbullying and encourage them to seek help when needed.